Traditions in world cinema - Badley, Linda; Palmer, R. Barton; Schneider, Steven Jay; Miller, Toby (Rutgers University Press, 2006)
Traditions in World Cinema brings together a colorful and wide ranging collection of world cinematic traditions—national, regional, and global—all of which are in need of introduction, investigation and, in some cases, critical reassessment. The movements described range from well-known traditions such as German expressionism, Italian neorealism, French, British, and Czech new wave, and new Hollywood cinema to those of emerging significance, such as Danish Dogma, postcommunist cinema, Brazilian post–Cinema Novo, new Argentine cinema, pre-independence African film traditions, Israeli persecution films, new Iranian cinema, Hindi film songs, Chinese wenyi pian melodrama, Japanese horror, and global found-footage cinema.